2010
DOI: 10.1089/ars.2009.3050
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Modulates Resveratrol-Induced ROS Production by Regulating Mitochondrial Respiration in Tumor Cells

Abstract: Resveratrol is a naturally occurring flavanoid with potent apoptosis-inducing activity against human tumor cells. We investigated the effect of resveratrol on human leukemia cell lines, in particular its ability to induce intracellular reactive oxygen species production and the effect of Bcl-2 overexpression on this model. Exposure of CEM cells to increasing concentrations of resveratrol (0-50 microM) resulted in an increase in mitochondrial superoxide production, decrease in transmembrane potential, and a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
0
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 32 publications
3
62
0
3
Order By: Relevance
“…8;2013 potential than in RSV 20 µg/mL treated group (Silva et al, 2012). The decrease in the mitochondrial membrane potential caused by RSV has been widely described in somatic cells and has allowed its use in cancer treatment since RSV is able i) to regulate the mitochondrial permeability transition pore (Zunino & Storms, 2006), ii) to increase the mitochondrial superoxide production (Low et al, 2010), iii) to decrease the mitochondrial membrane potential (Sareen et al, 2006;van Ginkel et al, 2007) and iv) to disrupt the mitochondrial respiratory chain (Zheng & Ramirez, 2000;Zini et al, 1999). The ATP content diminution in RSV treated boar spermatozoa is very clear in our study, falling between 3-6 times when using 33 µM RSV and 10 to 20 times when using 100 µM RSV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8;2013 potential than in RSV 20 µg/mL treated group (Silva et al, 2012). The decrease in the mitochondrial membrane potential caused by RSV has been widely described in somatic cells and has allowed its use in cancer treatment since RSV is able i) to regulate the mitochondrial permeability transition pore (Zunino & Storms, 2006), ii) to increase the mitochondrial superoxide production (Low et al, 2010), iii) to decrease the mitochondrial membrane potential (Sareen et al, 2006;van Ginkel et al, 2007) and iv) to disrupt the mitochondrial respiratory chain (Zheng & Ramirez, 2000;Zini et al, 1999). The ATP content diminution in RSV treated boar spermatozoa is very clear in our study, falling between 3-6 times when using 33 µM RSV and 10 to 20 times when using 100 µM RSV.…”
Section: Discussionmentioning
confidence: 99%
“…At present, a large number of studies show that the natural polyphenol resveratrol may be beneficial to many aspects of cell function and animal health; however, this compound displays a dichotomy: low doses can improve cell function while high doses increase cell death with a concomitant decrease in the mitochondrial membrane function (Fulda et al, 2010;Low et al, 2010;Pervaiz & Holme, 2009;Sareen et al, 2006;Zini et al, 1999;Zunino & Storms, 2006). Regarding male reproductive system, some studies have focused in the actions of resveratrol with divergent results (Branco et al, 2010;Collodel et al, 2011;Garcez et al, 2010;Juan et al, 2005;Ourique et al, 2013;Silva et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Increase of mitochondria permeability and cytochrome c release are frequently due to reactive oxygen species (ROS) [37,38] often involved in apoptosis triggered by chemopreventive agents [39]. Several studies have revealed prooxidant effects of plantderived polyphenols like flavonoids or resveratrol [39].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies showed that both resveratrol (Schilder et al, 2009;Low et al, 2010) and HDACIs (Ruefli et al, 2001;Rosato et al, 2010) could trigger cell death through an oxidative injury-mediated process. Therefore, the effects of resveratrol with or without HDACIs on the generation of reactive oxygen species (ROS) were examined.…”
Section: Resultsmentioning
confidence: 99%
“…Resveratrol has been associated with minimal toxicity, and plasma levels of Ͼ300 M are achievable and well tolerated among humans (Howells et al, 2011). In preclinical studies, resveratrol exhibited activity against various malignant cell types, including AML (Tsan et al, 2002), through diverse mechanisms such as inhibition of IKK and NF-B (HolmesMcNary and Baldwin, 2000), induction of oxidative injury (Low et al, 2010), and autophagy (Puissant et al, 2010). Resveratrol was shown to act as a Sirt1 agonist (Milne et al, 2007), although evidence indicating that this may involve indirect actions has emerged (Pacholec et al, 2010).…”
Section: Introductionmentioning
confidence: 99%